CYP2D6 Genotype-Based Dose Recommendations for Risperidone in Asian People - Cui, Yuanxia; Yan, Hao; Su, Yi; Wang, Lifang; Lu, Tianlan; Zhang, Dai; Yue, Weihua (Frontiers in Pharmacology, 2020)
In this study, we aimed to provide distinct dose recommendations for risperidone based on the genotypes of cytochrome P450 enzymes CYP2D6, especially for the Asian population. Firstly, we investigated the influence of CYP2D6 polymorphism on the pharmacokinetics of risperidone in Chinese patients with schizophrenia. Then, we searched several databases for studies covering the relationship between pharmacokinetics parameters of risperidone and the CYP2D6 genotype. Pooled pharmacokinetics parameters were meta-analyzed using a random-effects model. Lastly, we calculated the dose adjustment for risperidone based on CYP2D6 genotype for Europeans and Asians. Significant differences between the extensive metabolizer and intermediate metabolizer groups were observed for dose adjusted risperidone level, 9-hydroxyrisperidone level, and risperidone/9-hydroxyrisperidone ratio, but not for the total active moiety. Meta-analysis showed that significant differences were observed among the four phenotype groups, including steady state concentration, peak risperidone concentration, and the area under the curve, using Kruskal-Wallis test. No differences were found in oral clearance. For risperidone, the dose recommended for poor and ultra-rapid metabolizers of CYP2D6 for Asians was different compared to that for Caucasians for poor metabolizers (dose adjusted around 50% for Caucasians, but for Asians the risperidone dose should be reduced by 26%.). For ultra-rapid metabolizers, the risperidone dose should be increased about 38% for the Caucasians and 31% for Asians. This was a first attempt to apply novel pharmacogenetics to suggest dose-regimens for the Asian population. Additional research is required to further examine these findings.